Community Development: Optimizing The Independence Attitudes of Al Muttaqien Saving and Loan Cooperative Members - Saripah, Iip; Uyuandi, Agus Elga (Journal of Nonformal Education, 2021)
This research was conducted to obtain information about the optimization of the independent attitude from members of saving and loan cooperatives in terms of community empowerment context. This research was conducted at the KEBAL Al Muttaqien Saving and Loan Cooperative that involved the management and members as research subjects. This study uses a qualitative method with a case study approach. The information found from this research is the success of the management in implementing the improvement of members' independence by emphasizing the strengthening aspects such as material, intellectual, and management independence. It can be concluded that the development efforts have been made by prioritizing the capacity of the community to develop, be independent, and be able to manage the natural resources around them. Thus, empowerment activities are implemented so that people can participate in achieving independence. KSP KEBAL has performed its role as an empowerment agent to provide strength to the community as an empowered group. The independence of cooperative members is a measure of the successful efforts in carrying out its organizational and business activities.